Synthesis, Characterization and Study Biological Activity of Some New Compounds Derived From Phthalic Anhydride - Nebras M. Jamel (Journal of Global Pharma Technology, 2018)
In this research , phthallic anhydride ring is opened with 4-methyl aniline and acetone as a solvent to results the compound [I] that reacted with dimethyl sulphate and anhydrous sodium carbonate formation to phathalate ester [II], while the acid hydrazide compound [III], was obtained from mixed the compound [II]with hydrazine hydrate, Synthesis four type of shiff bases[IV]a-d was synthesized from the reaction of acid hydrazide [III] with aromatic aldehyde or ketone , when reacted Shiff bases with phthalic anhydride or naphthalicanhydride,I get eight derivatives of oxazepine [V]a-d , [VI]a-d. The bacterial activity of the new compounds studied by four species of bacteria: Esherichia Coli, Enterobactecloacae (Gram negative) and staphylococcusaureus, Bacillus subtilis (Gram positive). These compounds were identified by FTIR,1HNMR and Mass (of some of them).Keywords: Schiff bass, 1, 3-oxazepine and antibacterial activity.